Series 2: Development of a Multiplex Amplicon Next Generation Sequencing Assay for Rapid Assessment of Resistance-Associated Mutations in M. tuberculosis Clinical Cases - Adriana Cabrera; Tracy Lee; Kathleen Kolehmainen; Trevor Hird; Danielle Jorgensen; Calvin Ka-Fung Lo; Hasan Hamze; Alan O’Dwyer; Dan Fornika; Rupinder Kaur KhunKhun; Mabel Rodrigues; Natalie Prystajecky; et al. (Tropical Medicine and Infectious Disease, 2025)
Treatment of Mycobacterium tuberculosis requires multi-drug regimens, and resistance to any individual antibiotic can compromise outcomes. For slow-growing organisms like M. tuberculosis, rapid detection of resistance-conferring mutations enables timely initiation of effective therapy. Conversely, confirming wild-type status in resistance-associated genes supports confidence in standard regimens. We developed an amplicon-based next generation sequencing (amplicon tNGS) assay on the Illumina platform targeting eight genes linked to resistance to isoniazid, rifampin, ethambutol, pyrazinamide, and fluoroquinolones. Sequencing results were analyzed using a custom bioinformatics pipeline. Forty-seven samples were used for assay development, and 37 additional samples underwent post-implementation clinical validation. Compared to whole genome sequencing (WGS), amplicon tNGS demonstrated 97.7% sensitivity, 98.9% specificity, and 98.7% overall accuracy for variant detection in targeted regions. Resistance prediction showed 79.3% concordance with WGS; discrepancies were primarily due to mutations outside of target regions. Among post-implementation samples, 27/37 passed quality metrics for all targets, with 95.7% concordance between amplicon tNGS results and final susceptibility results. This assay is now in use in our laboratory and offers significantly faster turnaround than both WGS and phenotypic methods on cultured isolates, enabling more rapid, informed treatment decisions for tuberculosis patients.